Associations between lactate thresholds and 2000 m rowing ergometer performance: Implications for prediction—A systematic review - Kilbey, T.; Vecchi, E.; Salbany, P.; Handa, A.; Stride, E.; Sheth, M. (Sports Medicine - Open, 2025)
Background Various exercise thresholds have been evaluated to predict athlete performance. However, a systematic review of the literature assessing the association between lactate-based exercise thresholds and 2000 m rowing ergometer performance is still lacking. These may have utility in the prediction of 2000 m rowing ergometer performance due to the close relationship between metabolic parameters and development of endurance capacity. The aim of the present study is to review and assess the extent, quality, and reliability of lactate-based exercise testing and methodologies in their association with 2000 m rowing ergometer performance, and to discuss the potential implications for performance prediction.